Effect of Nabho Mudra on the salivary lipid profile and well-being of adolescents: A pilot study - Yazurved Sharma
Mudras are integral practices described in ancient Vedic texts. This feasibility study investigated the effects of Nabho Mudra (Yogic Mudra) practice on metabolism, assessed through salivary lipid profiles and the psychological well-being of adolescents. The study included 80 secondary school students from Central Delhi, randomized into experimental (n=40) and control (n=40) groups, with a mean age of 14.1 years. The experimental group underwent a structured 1 month Nabho Mudra practice protocol consisting of 10 min daily sessions, 6 days per week. Well-being assessment utilized the World Health Organization (WHO)-5 questionnaire, while salivary lipid profiles were analyzed in a subset of 20 students with Body Mass Index (BMI; kg/mp2(B)> 22 (representing 85th-95th percentiles on the WHO BMI-for-age chart). Post-intervention analysis revealed statistically significant improvements in the WHO-5 well-being index among the experimental group (p=0.05), whereas the control group showed no significant variation (p=0.2). Additionally, significant changes were observed in BMI (p=0.003) and Low-density lipoprotein (LDL) levels (p=0.05), accompanied by marked alterations in other salivary lipid parameters. These findings demonstrate the potential efficacy of Nabho Mudra as an intervention for enhancing physical and psychological well-being, while the observed changes in salivary lipid profiles warrant further investigation to elucidate the underlying mechanisms and broader health implications. Future longitudinal studies with larger cohorts are recommended to validate these preliminary findings and explore the therapeutic applications of this traditional yogic practice.s